Usulan Perbaikan Perencanaan dan Pengendalian Produksi di Konveksi Rima Collection - Rizal Alfarizki; Nita P. A. Hidayat (Bandung Conference Series: Industrial Engineering Science, 2024)
Abstract. Rima Collection, a company specializing in the production of Islamic clothing and school uniforms, is facing challenges in production planning and control. The company struggles with optimizing production targets for its Islamic clothing line and experiences delays in product delivery for its school uniform line. This research aims to analyze the current state of production planning and control, identify the negative impacts of suboptimal planning, and provide recommendations for improvement. The methods used include forecasting, standard time measurement, aggregate planning, master production scheduling, Rough Cut Capacity Planning (RCCP), Material Requirement Planning (MRP), and Capacity Requirement Planning (CRP). The findings reveal that the current production target setting relies on estimations and business instincts rather than on hist orical data or accurate forecasting methods. As a result, the company faces issues of overstock or stock shortages, leading to increased storage costs and missed sales opportunities. The research recommends improvements through the application of demand forecasting, MRP, and CRP methods. It also provides a detailed production plan and schedule for 2024, including material requirements and an analysis of production capacity to ensure that all resources and infrastructure can support the achievement of the set production targets. Abstrak. Rima Collection, sebuah perusahaan konveksi pakaian gamis dan seragam sekolah, menghadapi masalah dalam perencanaan dan pengendalian produksi. Pada lini produksi gamis, perusahaan mengalami kesulitan dalam menentukan target produksi yang optimal, sementara pada lini seragam sekolah, terdapat keterlambatan pengiriman produk. Penelitian ini bertujuan untuk menganalisis kondisi perencanaan dan pengendalian produksi saat ini, mengidentifikasi dampak negatif dari perencanaan yang kurang optimal, serta memberikan rekomendasi perbaikan. Metode yang digunakan meliputi peramalan, pengukuran waktu baku, perencanaan agregat, jadwal induk produksi, Rough Cut Capacity Planning (RCCP), Material Requirement Planning (MRP), dan Capacity Requirement Planning (CRP). Hasil penelitian menunjukkan bahwa penentuan target produksi saat ini tidak didasarkan pada data historis atau metode peramalan yang akurat, melainkan hanya berdasarkan perkiraan dan insting bisnis. Akibatnya, terjadi kelebihan atau kekurangan stok yang berdampak pada peningkatan biaya penyimpanan dan potensi kehilangan peluang penjualan. Penelitian ini merekomendasikan perbaikan melalui penggunaan metode peramalan permintaan, MRP, dan CRP. Penelitian juga menghasilkan perencanaan produksi dan jadwal produksi terperinci untuk tahun 2024, termasuk kebutuhan material dan analisis kapasitas produksi yang memastikan bahwa semua sumber daya dan infrastruktur dapat mendukung pencapaian target produksi.